Duplication and Loss of Function of Genes Encoding RNA Polymerase III Subunit C4 Causes Hybrid Incompatibility in Rice. Issue 8 (1st August 2017) - Nguyen, Giao Ngoc; Yamagata, Yoshiyuki; Shigematsu, Yuko; Watanabe, Miyako; Miyazaki, Yuta; Doi, Kazuyuki; Tashiro, Kosuke; Kuhara, Satoru; Kanamori, Hiroyuki; Wu, Jianzhong; Matsumoto, Takashi; Yasui, Hideshi; et al.
Abstract: Reproductive barriers are commonly observed in both animals and plants, in which they maintain species integrity and contribute to speciation. This report shows that a combination of loss-of-function alleles at two duplicated loci, DUPLICATED GAMETOPHYTIC STERILITY 1 ( DGS1 ) on chromosome 4 and DGS2 on chromosome 7, causes pollen sterility in hybrid progeny derived from an interspecific cross between cultivated rice, Oryza sativa, and an Asian annual wild rice, O. nivara . Male gametes carrying the DGS1 allele from O. nivara ( DGS1-nivara s ) and the DGS2 allele from O. sativa ( DGS2-T65 s ) were sterile, but female gametes carrying the same genotype were fertile. We isolated the causal gene, which encodes a protein homologous to DNA-dependent RNA polymerase (RNAP) III subunit C4 (RPC4). RPC4 facilitates the transcription of 5S rRNAs and tRNAs. The loss-of-function alleles at DGS1-nivara s and DGS2-T65 s were caused by weak or nonexpression of RPC4 and an absence of RPC4, respectively. Phylogenetic analysis demonstrated that gene duplication of RPC4 at DGS1 and DGS2 was a recent event that occurred after divergence of the ancestral population of Oryza from other Poaceae or during diversification of AA-genome species.